Implementation of the Problem Based Learning Strategy in Islamic Religious Education Learning in Improving Students' Higher Order Thinking Skills - Nuraini, Ririn (Civiliza Publishing, Indonesia., 2025)
This research was driven by the researcher’s concern over the rapid development of the digital era, which demands that teachers equip students with critical thinking skills to face emerging challenges. Higher order thinking skills are essential for students to adapt to technological advances while maintaining a strong foundation in Islamic Religious Education values. This study aims to examine the implementation of the Problem Based Learning (PBL) strategy in Islamic Religious Education at State Vocational High School 1 Ponorogo and its impact on enhancing students' higher order thinking skills. Using a qualitative approach and case study design, data were collected through in-depth interviews, non-participatory observations, and documentation. The data were analyzed using Miles and Huberman’s interactive model: data collection, reduction, display, and conclusion drawing. Validity was ensured through triangulation. The findings show that PBL was implemented through five stages: setting objectives and presenting problems, forming groups, guiding group work, student presentations, and evaluation. The implementation of PBL had a significant positive impact on students' cognitive, affective, and psychomotor development. Moreover, it enhanced students’ critical thinking and problem-solving abilities in learning Islamic Religious Education. Overall, PBL proved to be an effective strategy in fostering higher order thinking among students in the digital age.